2017
DOI: 10.3390/ijerph14121445
|View full text |Cite
|
Sign up to set email alerts
|

Lead Emissions and Population Vulnerability in the Detroit (Michigan, USA) Metropolitan Area, 2006–2013: A Spatial and Temporal Analysis

Abstract: Objective: The purpose of this research is to geographically model airborne lead emission concentrations and total lead deposition in the Detroit Metropolitan Area (DMA) from 2006 to 2013. Further, this study characterizes the racial and socioeconomic composition of recipient neighborhoods and estimates the potential for IQ (Intelligence Quotient) loss of children residing there. Methods: Lead emissions were modeled from emitting facilities in the DMA using AERMOD (American Meteorological Society/Environmental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 41 publications
2
28
0
Order By: Relevance
“…As mentioned earlier, previous research has demonstrated Black children are exposed to more Pb during early childhood, while an increasing and higher percent Black population is associated with greater amounts of environmental Pb exposure and more blood Pb among children. Higher airborne Pb emissions are correlated with increasing racial segregation of the Black population in the Detroit metropolitan area, which is a stronger predictor than poverty levels [48], while the authors also noted that unequal enforcement of environmental laws, emission standards, and remediation efforts by regulators in addition to facility siting preference by industry appear to play significant roles in these local racial disparities.…”
Section: Persistent Racial Disparity In Risk Factorsmentioning
confidence: 94%
See 3 more Smart Citations
“…As mentioned earlier, previous research has demonstrated Black children are exposed to more Pb during early childhood, while an increasing and higher percent Black population is associated with greater amounts of environmental Pb exposure and more blood Pb among children. Higher airborne Pb emissions are correlated with increasing racial segregation of the Black population in the Detroit metropolitan area, which is a stronger predictor than poverty levels [48], while the authors also noted that unequal enforcement of environmental laws, emission standards, and remediation efforts by regulators in addition to facility siting preference by industry appear to play significant roles in these local racial disparities.…”
Section: Persistent Racial Disparity In Risk Factorsmentioning
confidence: 94%
“…Black race remains a strong independent predictor of more blood Pb throughout childhood [39][40][41][42][43][44][45][46]. Geospatial analyses have demonstrated that increasing concentrations of exposure to Pb from the air, soil, water, or industrial releases are associated with early childhood BLLs [47][48][49][50][51][52][53][54], while an increasing percent Black population is a strong predictor for higher blood Pb among young children in US cities, states, and nationwide across the US [32][33][34]39,40,53,[55][56][57][58][59][60][61][62][63]. Black children in the US are exposed to more Pb from their environment [47][48][49][50][64][65][66][67][68][69].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, lead poisoning is still a concern of public health in the inner and old industrial cities. The urban environment usually suffers from historically emitted leaded gasoline, smelters, iron and steel production, lead-acid-battery manufacturing, nonferrous (brass and bronze) foundries, landfills, waste incinerators, sewage sludge incinerators, hazardous waste sites, power plants (refineries/coal burning), and older homes that contain lead based paint/pipes [ 18 ]. Studies have shown that the incident rate of children’s lead poisoning was associated with environmental lead hazard exposure and socio-economic status such as the population density, proportion of houses built before 1950, percentage of poverty level and minority [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%